More than a name: Heterogeneity in characteristics of models of maternity care reported from the Australian Maternity Care Classification System validation study. Issue 4 (August 2017) - Donnolley, Natasha R.; Chambers, Georgina M.; Butler-Henderson, Kerryn A.; Chapman, Michael G.; Sullivan, Elizabeth A.
Abstract: Background: Without a standard terminology to classify models of maternity care, it is problematic to compare and evaluate clinical outcomes across different models. The Maternity Care Classification System is a novel system developed in Australia to classify models of maternity care based on their characteristics and an overarching broad model descriptor (Major Model Category). Aim: This study aimed to assess the extent of variability in the defining characteristics of models of care grouped to the same Major Model Category, using the Maternity Care Classification System. Method: All public hospital maternity services in New South Wales, Australia, were invited to complete a web-based survey classifying two local models of care using the Maternity Care Classification System. A descriptive analysis of the variation in 15 attributes of models of care was conducted to evaluate the level of heterogeneity within and across Major Model Categories. Results: Sixty-nine out of seventy hospitals responded, classifying 129 models of care. There was wide variation in a number of important attributes of models classified to the same Major Model Category. The category of ' Public hospital maternity care ' contained the most variation across all characteristics. Conclusion: This study demonstrated that although models of care can be grouped into a distinct set of Major Model Categories, there are significant variations in models of the same type. This could result in seemingly 'like' models of care being incorrectly compared if grouped only by the Major Model Category.